Effectiveness of Implementing E-module Based on Contextual Teaching and Learning to Improve Learning Outcomes and Class XI IPS in SMA Negeri 1 Soe - Didimus Febi Erwin Talan; Ani Widayati (Pelopor Publikasi Akademika, 2023)
Effectiveness of Contextual-Based E-Module Application Teaching And Learning To Improve Learning Activities, Learning Outcomes And Critical Thinking Ability Of Students In The Eyes Of Economics Students Class X I IPS SMA Negeri 1 Soe This research aims to determine the Effectiveness of The Application of E-Module Based on Contextual Teacing And Learning To Increase Learning Activities, Learning Outcomes andStudents' Critical Thinking Ability in ABPD and APBN materials in the Eyes of Economics Students Class X I I PS SMA Negeri 1 Soe. This research is a pseudo-experimental research with one-group pretest and posttest design research design. The experimental class was treated by applying an e-module model based on the contextual teaching and learning model while the control class was treated by applying a conventional learning model. Data analysis used the manova test with a significance level of 5%. The results showed that there was a difference in student learning activities in economics subjects between classes that did not apply contextual teaching and learning-based e-modules , there was a significant value of 0.0 16 or < 0.05 and those that appliede-module Based on contextual teaching and learning, there is a significant value of 0.000 or < 0.05.